INNOVATIVE CLUSTER METHOD IN THE PROCESS OF PRODUCTION AND SALE OF AGRICULTURAL PRODUCTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article develops a generalized and expanded definition of the need for the organization of the cluster in agriculture and the study of the principles, conditions, and theoretical views of development.